UTILIZATION OF PALM OIL SHELL WASTE AS ALTERNATIVE ADDITIVES IN MANUFACTURING PAVING BLOCK - Wiratno; Samuel Layang; Wandra Prima Pera (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2020)
Palm shells are one of the wastes produced from the processing of crude palm oil in addition to empty fruit bunches and coir which account for 60% of oil production. Palm oil shell waste is widely used as active charcoal in the oil, rubber, sugar, and pharmaceutical industries. The potential of palm oil shell waste in Indonesia is very large considering the area of oil palm plantations which continues to increase every year. This study aims to determine the percentage of the addition of palm oil shell waste in the manufacture of paving blocks that provide optimum compressive strength and water absorption values from several variations of the addition of palm oil shell waste that replaces some of the fine aggregates. The study was carried out experimentally in a laboratory using a boxed specimen with a length of 20 cm, a width of 10 cm, a height of 6 cm by 40 pieces. The mixture uses a ratio of 1 cement and 5 sand with fas 0.3. Treatment of test specimens by immersion in water for further testing of compressive strength and absorption at the age of 28 days. Based on testing of the compressive strength of paving blocks with a percentage of 0%, 5%, 10%, 15% are respectively 8.08 MPa, 7.18 MPa, 6.46 MPa, 5.94 MPa. The value of paving block water absorption with a percentage of 0%, 5%, 10%, 15% are respectively 9.88%, 10.25%, 12.27%, 12.44%.